Prevalence and factors of Sunscreen Use in Medical and Paramedical Students : A Cross-Sectional Study in Punjab, Pakistan - Amin, Uzma; Rana, Mahwash; Faiz, Farzana; Saleem, Zaheer; Aslam, Shazia (Journal of Pakistan Association of Dermatologists, 2023)
Background: Exposure to environmental ultraviolet radiation (UVR) has many adverse biological effects on the human body which comprise of cutaneous aging and cutaneous carcinogenesis. These can be minimized by regular use of photoprotective measures especially when started at a young age. This study was conducted to assess the knowledge, outlook and perceptions about sunscreens and photoprotective measures in medical and allied health science students. Methods: The data was collected using an online questionnaire distributed among medical and paramedical students of various government institutes of Punjab via WhatsApp groups over a four months. Results: A total of 437 students responded which consisted of 63% females and 37% males with a prevalence of use in 48%. Most of the participants were aged between 20-30 years (66%) and lived in urban area (72%). About half did not use sunscreens and only 17% used sunscreens on a daily basis. The main purpose of using sunscreens was prevention of skin darkening (65%). About two-thirds had experienced side effects with sunscreen use. About half knew about the time and sites of application but more than two-thirds did not have any idea of re-application timings. Conclusion: Prevalence of sunscreen use in medical and paramedical students of Punjab was 48% with a large ratio not having sufficient knowledge of sunscreen use and practice. Practical Implications: Future awareness activities can be planned focusing on identifying the gaps in knowledge and misconceptions of medical and paramedical students so as to increase sunscreen usage. Key words prevalence, sunscreen, photoaging